Priming of wheat plant with weed extracts, calcium and salicylic acid for contribution to alleviating the oxidative stress imposed by Fusarium graminearum and lead toxicity - Sherien E. Sobhy; Dalia G. Aseel; Essam-Eldeen M. Abo-Kassem; Nasser A. Sewelam; Khalil M. Saad-Allah; Marwa A. Samy; Elsayed E. Hafez (Novel Research in Microbiology Journal)
Biotic and abiotic stress factors drastically limit plant growth and productivity through changing the physiological, biochemical, and cellular processes. In this study, 100 mM of lead (Pb) was used as an abiotic stress source, while Fusarium graminearum represented a biotic one on wheat plant. Compared to the control, Pb treatment and F. graminearum inoculation led to remarkable reductions in the wheat seedlings leaf area that reached 21 %, and 12.5 %, respectively. Moreover, the current results showed an enhanced activity of Phenylalanine ammonia lyase (PAL) that reached 173 % in the stressed wheat grains and seedlings, decreased mineral contents in N-3, P+3, K+, and Ca+2 in the shoot of wheat seedlings by 25, 42, 23 and 44 %; respectively, substantial increase (79 %) in the total soluble carbohydrates (TSC) and a highly significant reduction (28 %) in the total soluble proteins (TSP), compared with the non-treated control plants. On the other hand, wheat seed priming with weed extracts [i.e., Portulaca oleracea L. (purslane) and Beta vulgaris L. (chard)], or chemical solutions; mainly Calcium (Ca+2) and Salicylic acid (SA) applied exogenously, resulted in a noteworthy increase in the leaf area, compared with the stress treatments. Furthermore, seed priming ameliorated the toxic effects induced by Pb and F. graminearum treatments on the photosynthetic pigments; where it significantly increased the pigments content, while the chlorophyll (Chl) a/b ratio was reduced. Furthermore, priming treatments significantly increased the mineral contents (i.e., N, P, K, and Ca) and counteracted the imposed effects of stress treatments on TSC and TSP. The differential display polymerase chain reaction (DD-PCR) technique was performed to identify the variations in gene expression between the different treatments of wheat plants at three intervals of 7, 14, and 21 d old. This study aimed to investigate the use of plant extracts as potentially effective and environmentally safe green bio-control agents to control the infection of wheat plant by F. graminearum, ameliorate the biotic and abiotic stresses, and compete with the currently used deleterious chemical fungicides in the wheat farms.